Possession vs. goal scoring during small-sided games in soccer: a narrative mini-review on the effects on physiological, physical, technical and tactical performance - Rumpf, M. C.; Jäger, J.; Lloyd, R.; Lochmann, M. (Frontiers in Sports and Active Living, 2026)
Different task constraints such as possession play and goal scoring are regularly utilized in small-sided games (SSG) in order to train game specific situations. This narrative mini-review aimed to summarize how these two task constraints influence players' physiological, physical, technical and tactical parameters during SSG. Possession games increase the physiological load of players. Variables such as mean (+4.35%) and max heart rate (+6.43%) as well as duration >90%HRmax (+39.7%) were significantly higher compared to scoring format SSG. Players also felt significantly greater subjective exertion (+24.2%), mental challenge (+18.4%) and lower enjoyment (-6.45%) in comparison to scoring games, especially when goalkeepers participated. Possession games also increased physical strain for players during SSG, with total (+12.6%) and relative (+8.43%) running distance, average moving speed (+14.2%), number of low (+35.9%) and high ACC (+23.6%), and distances in high(er) speed bands (>14 km/h) being more prominent in possession games. Players are technically more engaged in possession format SSG. Significantly more total (+38.7%) and individual (+60.4%) ball touches, number of passes (+99.0%), and passes per player (+55.8%) were observed in possession compared to scoring games. The scarce scientific evidence regarding the effect of possession games on tactical variables suggests that more players are involved for a longer period of time exploring greater space during these types of games. Coaches should apply possession games to increase physiological, physical, and technical engagement of players during SSG.